hộ mik nha
a)\(2.x-\frac{3}{2}=\frac{1}{2}\)
\(2x=\frac{4}{2}\)
\(x=\frac{4}{2}:2\)
\(x=1\)
Vậy x=1
b)\(\frac{8}{13}.x+\frac{5}{13}.x=\frac{1}{10}\)
\(x.\left(\frac{8}{13}+\frac{5}{13}\right)=\frac{1}{10}\)\
\(x.1=\frac{1}{10}\)
\(x=\frac{1}{10}\)
Vậy x=\(\frac{1}{10}\)
c)\(\frac{2}{15}+\frac{7}{15}.x=\frac{1}{15}\)
\(\frac{7}{15}x=\frac{-1}{15}\)
x=\(\frac{-1}{7}\)
Vậy \(x=\frac{-1}{7}\)
\(\frac{3}{2}\cdot x-\frac{3}{2}=\frac{1}{2}\) \(\frac{8}{13}\cdot x+\frac{5}{13}\cdot x=\frac{1}{10}\)
\(\frac{3}{2}\cdot x=\frac{3}{2}+\frac{1}{2}=2\) \(\left[\frac{8}{13}+\frac{5}{13}\right]\cdot x=\frac{1}{10}\)
\(x=2:\frac{3}{2}\) \(1\cdot x=\frac{1}{10}\)
x=\(\frac{4}{3}\) \(x=\frac{1}{10}:1\)
Vậy x=\(\frac{4}{3}\) \(x=\frac{1}{10}\)
Vậy x=\(\frac{1}{10}\)
c,\(\frac{2}{5}+\frac{7}{15}\cdot x=\frac{1}{15}\)
\(\frac{7}{15}\cdot x=\frac{1}{15}-\frac{2}{5}=\frac{-1}{3}\)
\(x=\frac{-1}{3}:\frac{7}{15}\)
\(x=\frac{-5}{7}\)
Vậy x=\(\frac{-5}{7}\)